Association between youth involvement in home/community gardening and health behaviors - Perrault, Ashley, author; Li, Kaigang, advisor; Butki, Brian, committee member; Braungart-Rieker, Julia, committee member (Colorado State University. Libraries, 2024)
American youth are developing risk factors for historically "adult diseases" at increasingly high rates. These risk factors, such as obesity, elevated blood lipid, blood pressure and insulin resistance, put children at a high risk for developing chronic disease early in life, including before reaching adulthood. School gardening programs are effective at improving dietary intake, physical activity levels and BMI of youth. Despite the success of such programs, there is a need for interventions that effectively target child behaviors while at home. Family-based home and/or community gardens may promote child health behaviors similar to those that occur in school-based gardening programs. A home and/or community garden has the added benefit of parental involvement, which has been shown to be essential for effective child health interventions. The current study examined the relationship between youth involvement in a home and/or community garden and various health behaviors. A convenience sample of 124 adults participated in a cross-sectional survey from June – October 2023. Participants answered questions about family and child involvement in a home/community garden, child health behaviors and parent health behaviors. Health behaviors assessed were physical activity minutes, sedentary behavior, frequency of fruit and vegetable intake and mental health symptoms. Independent sample t-tests indicated that gardening youth had lower sedentary time (t(112) = -1.95, p = 0.03), as well as higher frequency of fruit (t(110) = 2.14, p = 0.02) and vegetable intake (t(109) = 2.67, p = 0.004). Parent fruit intake had a positive linear association with child fruit intake (β = 0.51, p = <0.001), as did parent gardening belief (β = 4.04, p = 0.01). Mediation analysis indicated a positive association between path a (gardening status and parent fruit intake: β=3.06, 95% CI: 0.08, 6.03, p = 0.04) and path b (parent fruit intake and child fruit intake: β = 0.48, 95% CI: 0.30, 0.65, p = <0.001). Gardening status was no longer associated with child fruit intake after the inclusion of parent intake (c': β = 1.64, 95% CI: -1.06, 4.35, p = 0.23), suggesting that parental fruit intake fully mediated the relationship between gardening status and child fruit intake. Gardening status had a positive linear association with child vegetable intake (β = 3.4, p = 0.02), as did parent vegetable intake (β = 0.21, p = 0.004). These findings indicate that youth involvement in a family-based home and/or community garden may be associated with positive health outcomes, especially regarding dietary intake. Parental influence was also associated with positive youth health outcomes. Our findings suggest that home and/or community gardens may provide an effective technique for child health interventions.
Keywords: gardening; parent; child health; physical activity; nutrition